Polynucleobacter rarus sp. nov., a free-living planktonic bacterium isolated from an acidic lake - Hahn, Martin W. (2010)
The heterotrophic, aerobic, facultatively anaerobic under denitrifying conditions, catalase- and oxidase-positive, non-motile strain MT-CBb6A5(T), which was isolated from an acidic lake located in Wisconsin (USA), was characterized. The strain grew on NSY medium over a temperature range of 15–30 °C and a NaCl range of 0.0–0.3 % (w/v). The predominant fatty acids were C(16) : 0,C(18 : 1)ω7c, 11-methyl C(18 : 1)ω7c, feature 3 (including C(16 : 1)ω7c), and feature 2 (including C(14 : 0) 3-OH). The DNA G+C content of the strain was 40.3 mol%. Phylogenetic analysis as well as strong similarities in phenotypic and chemotaxonomic traits indicated the affiliation with the genus Polynucleobacter. 16S rRNA gene sequence similarity values with the two described species of the genus Polynucleobacter ranged from 95.6 to 96.0 %. The strain differs from the two described species of the genus Polynucleobacter in the ability to assimilate oxalic and glycolic acids, and in the presence of the fatty acids C(15 : 1)ω8c and C(16 : 0) 3-OH as well as in quantitative differences in fatty acid composition. It has to be assumed that the strain shares with other free-living bacteria of the genus Polynucleobacter a planktonic lifestyle in the water column of freshwater habitats. Based on the phylogeny revealed and the chemotaxonomic and phenotypic differences from Polynucleobacter necessarius and Polynucleobacter cosmopolitanus, we propose to establish the novel species Polynucleobacter rarus sp. nov. with the type strain MT-CBb6A5(T) (=DSM 21648(T) =CIP 109928(T)).